Absolute Essentials of Project Management - Roberts, Paul (Ascent Audio, 2021)
Contemporary organizations proliferate with projects. Managing projects, working with project managers, and delivering project excellence have become fundamental skills in the world of business, resulting in an array of approaches, tools, and techniques that can bewilder. This book homes in on the absolute essential elements of the field. With practical insights throughout, the book provides listeners with a concise understanding of key concepts, techniques, and outcomes such as ownership, execution, success, quality, budgets, and risks. Authored by an experienced project and change management practitioner, consultant, and educator, this unique resource will be essential for students of project management looking to excel in employment.